Przemiany stosunków wodnych w dolinie górnej Noteci do połowy XIX wieku związane z antropopresją - Kaniecki, Alfred (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
The start of the great drainage work in the Upper Noteć valley is connected with the construction of the Bydgoszcz Canal in the years 1772–1774. Earlier, the economic ventures, like building of water mills or causeways, affected the area water conditions only locally. A reconstruction of the initial look of the valley still rests on historical source materials because no research has been conducted in the region to date. Here, we made use of the information from the 15th-century chronicle by Jan Długosz, of the description the 18th-century causeways, of the cartographic works of this period as well as the old descriptions of the Noteć valley. Despite attempts at a regulation of the channel, the Noteć valley from Lake Gopło to Nakło preserved its natural character until the mid-19th century, hence it was poorly accessible and swampy. It was only in the other half of the 19th century that the water conditions and the pattern of stream network in the Noteć valley were transformed radically owing to the drainage of wetland and the regulation of the river for navigational purposes.
Keywords: Drainage system; Human impact; Changes of discharges; Changes of level lakes